Leveraging Nano Block-Lattice for Cost-Effective Large-Scale Wi-Fi-Based IoT Network Expansion - Tiruvayipati, Sujanavan; Yellasiri, Ramadevi (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The rapid expansion of Internet of Things (IoT) networks necessitates cost-effective and scalable solutions for secure data transmission and storage. This study explores the integration of Nano (XNO) cryptocurrency with Wi-Fi repeater networks to address the challenges of IoT scalability and data security. By leveraging XNO’s block-lattice structure, this study demonstrates how the cryptocurrency’s minimal transaction fees, high transaction throughput, and low latency make it an optimal solution for real-time IoT data handling. In combination with Wi-Fi repeater networks, which extend coverage and reduce signal loss, the proposed system enables secure, decentralized storage of IoT data. Performance metrics, including latency, transaction throughput, and cost, show that the XNO-integrated IoT network outperforms traditional blockchain technologies such as Ethereum and IOTA, offering a promising solution for large-scale IoT deployments.